Quantification of creatine kinase reaction rate in mouse hindlimb using phosphorus‐31 magnetic resonance spectroscopic fingerprinting. (27th October 2020) - Kim, Kihwan; Gu, Yuning; Wang, Charlie Y.; Clifford, Bryan; Huang, Sherry; Liang, Zhi‐Pei; Yu, Xin
Abstract : Abstract The goal of this study was to evaluate the accuracy, reproducibility, and efficiency of a 31 P magnetic resonance spectroscopic fingerprinting ( 31 P‐MRSF) method for fast quantification of the forward rate constant of creatine kinase (CK) in mouse hindlimb. The 31 P‐MRSF method acquired spectroscopic fingerprints using interleaved acquisition of phosphocreatine (PCr) and γATP with ramped flip angles and a saturation scheme sensitive to chemical exchange between PCr and γATP. Parameter estimation was performed by matching the acquired fingerprints to a dictionary of simulated fingerprints generated from the Bloch‐McConnell model. The accuracy of 31 P‐MRSF measurements was compared with the magnetization transfer (MT‐MRS) method in mouse hindlimb at 9.4 T ( n = 8). The reproducibility of 31 P‐MRSF was also assessed by repeated measurements. Estimation of the CK rate constant using 31 P‐MRSF (0.39 ± 0.03 s −1 ) showed a strong agreement with that using MT‐MRS measurements (0.40 ± 0.05 s −1 ). Variations less than 10% were achieved with 2 min acquisition of 31 P‐MRSF data. Application of the 31 P‐MRSF method to mice subjected to an electrical stimulation protocol detected an increase in CK rate constant in response to stimulation‐induced muscle contraction. These results demonstrated the potential of the 31 P‐MRSF framework for rapid, accurate, and reproducible quantification of the chemical exchange rate of CK in vivo. Abstract : The forward rate constant of creatine kinase was quantified in mouse hindlimb using a novel 31 P magnetic resonance spectroscopic fingerprinting method. The results showed similar parameter estimation compared with the conventional magnetization transfer method, with significantly improved reproducibility and acquisition efficiency.